PERBEDAAN PENGARUH PEMBELAJARAN LOMPAT JAUH TERHADAP HASIL BELAJAR LOMPAT JAUH GAYA JONGKOK PADA SISWI PUTRI KELAS III SEKOLAH DASAR - Titin Kuntum Mandalawati (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2015)
The purpose of this study was to determine differences in effect learning to use tools longjump rope and circle as high stimulation and distance gradually towards results learnlong jump squat style. This study used an experimental method. Experiment by using preand post test. The study consisted of two groups: tools strap (A) and the group as a circlehigh stimulation (B). This study population is third grade Elementary School 1 PanggungBarat Magetan 2015. The average results of the study group pretest tools strap (A)amounted to 84.1 and group as circle high stimulation 82.4 (B), initial conditions showedtwo groups with similar capabilities. The average post test group tools strap (A)amounted to 156.8 and the group as a circle high stimulation 151.4 (B). Based on theresults obtained the following conclusions there is a significant difference between thelong jump learning using 2 tools and circle as high stimulation and distance graduallytowards learning outcomes long jump squat style on third grade Elementary School 1Panggung Barat Magetan 2012/2013. By p (0.034 < 0.05). Long jump teaching methodsusing tools ropes with better results.